The Influence of the Reading Literacy Program and Reading Habits on Student Learning Outcomes at Lamteh State Elementary School, Aceh Besar Regency - Dian Elyta; Musdiani Musdiani; Sariakin Sariakin (FKIP - Universitas Riau, 2026)
This study examined the influence of reading literacy programs and reading habits on students’ learning outcomes at Lamteh State Elementary School, Aceh Besar Regency, Indonesia. The research was motivated by the importance of literacy activities in improving students’ academic achievement and reading culture at the elementary school level. A quantitative approach with a causal associative design was employed in this study. The population consisted of 106 upper-grade students, while 84 students were selected as research samples using probability sampling through a simple random sampling technique. Data were collected using Likert-scale questionnaires and learning achievement tests. Statistical analysis was conducted using multiple linear regression analysis with the assistance of SPSS version 26. The findings revealed that reading literacy programs had a positive and significant influence on students’ learning outcomes with a t-count value of 2.506 and a significance value of 0.006. Reading habits also showed a positive and significant influence with a t-count value of 4.023 and a significance value of 0.000. Simultaneous testing demonstrated that reading literacy programs and reading habits significantly influenced students’ learning outcomes with an F-count value of 8.630 and a significance value lower than 0.05. The findings indicate that strengthening literacy programs and developing positive reading habits contribute to improving students’ academic achievement.